Analysis of Yamaha Scorpio Engine Performance with Variation of Ethanol Fuel and Shell V Power - Zufri Hasrudy Siregar (International Journal of Research in Vocational Studies (IJRVOCAS), 2023)
The number of motorized vehicles used will also be as much as the use of fossil fuels, as well as the increasing growth of vehicles that increases year by year, which does not affect fuel consumption but population growth. Fuel quality is measured by RON, where the higher the octane value, the better the fuel quality. RON simply describes how much pressure can be exerted before gasoline spontaneously ignites in the combustion chamber of the vehicle. This study aimed to determine the effect of Power, torque and fuel consumption with a mixture of Petalite, Shell V-Power and Ethanol with a test object, namely the Yamaha Scorpio motor. The research method used is a quantitative approach with a type of development research. The result of this study is that Shell V Power fuel, when mixed with ethanol will produce better engine performance, the greater the percentage of methanol introduced into the fuel, the better the performance produced, both torque, power, and fuel consumption, namely at rpm 1000,1500,2000,2500 methanol 8% the most optimal where the time is 174 Sec, Sec 105, Sec 86, Sec 51 Sec. And the force on the Load Cell is 0.535, 0.875, 1.102, 1.421 kgf.